Monetary policy rule and taylor principle in Mongolia: GMM and DSGE approaches - Hiroyuki Taguchi; Ganbayar Gunbileg (International Journal of Financial Studies, 2020)
This article aims to examine the monetary policy rule under an inflation targeting in Mongolia with a focus on its conformity to the Taylor principle, through two kinds of approaches: a monetary policy reaction function by the generalized-method-of-moments (GMM) estimation and a New Keynesian dynamic stochastic general equilibrium (DSGE) model with a small open economy version by the Bayesian estimation. The main findings are summarized as follows. First, the GMM estimation identified an inflation-responsive rule fulfilling the Taylor principle in the recent phase of the Mongolian inflation targeting. Second, the DSGE-model estimation endorsed theGMMestimation by producing a consistent outcome on the Mongolian monetary policy rule. Third, the Mongolian rule was estimated to have a weaker response to inflation than the rules of the other emerging Asian adopters of an inflation targeting.
Keywords: E52; E58; O53; 330; monetary policy rule; Taylor principle; Mongolia; inflation targeting; GMM; the New Keynesian DSGE model